Toll-Like Receptors 2, 4, and 7, Interferon-Gamma, Interleukin 10, and Programmed Death Ligand 1 Transcripts in Leishmanin Skin Test-Positive Reactions of Ibizan Hound Dogs - Laura Ordeix; Sara Montserrat-Sangrà; Pamela Martínez-Orellana; Laia Solano-Gallego (Journal of Immunology Research)
The leishmanin skin test (LST) is an in vivo technique commonly used to evaluate the Leishmania-specific cellular immune response in dogs. However, information regarding the local immune response in LST-positive reactions is scarce. We examined the pattern of toll-like receptor 2 (TLR2), TLR4, TLR7, interleukin- (IL-) 10, interferon gamma (IFN-γ), and (program death ligand) PD-L1 gene expression in LST-positive reactions and paired normal-looking skin of nine infected Ibizan hound dogs. Healthy skin from ten seronegative dogs from a nonendemic area was analysed as a negative control. Immune gene expressions were examined by quantitative PCR (qPCR) analysis. LST-positive reactions presented significant upregulation of TLR2, TLR4, IL-10, IFN-γ, and PD-L1 and downregulation of TLR7 when compared with healthy skin of seronegative control dogs from a nonendemic area. All transcripts but TLR7 were significantly higher in LST-positive reaction than in paired normal-looking skin of Ibizan hound. The expression profile of immune genes in LST-positive reactions was similar to that previously observed in clinically lesioned skin of mildly diseased dogs with papular dermatitis due to Leishmania infantum infection. This data provide additional support for the important role of TLRs in canine leishmaniosis.